Analisis Strategi Kepala Sekolah Dalam Meningkatkan Kesejahteraan Guru Non PNS - Dian Safitri; Moh. Toharudin; Diah Sunarsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
A leader in a school, the principal must have a complete vision, mission, and strategy in order to be able to provide responsibility for managing resources and developing strategies, especially in financial management to achieve teacher competence. Being a principal must always have a strategy for the welfare of teachers. This study aims to describe the principal's strategy as a manager, the principal's strategy as an administrator, and the form of welfare provided by the principal in improving the welfare of non-civil servant teachers. The method used in this study is a qualitative approach with the subject of principals and non-civil servant teachers. The techniques used to collect data are observation, interviews, and documentation. The analysis technique used is source triangulation technique and technique triangulation. Data analysis techniques in this study are data collection, data reduction, data presentation, and drawing conclusions. The results of the study show: 1) the principal's strategy as a manager in improving the welfare of non-civil servant teachers is that the principal manages educators through teacher professional development activities including training seminars, workshops, and KKG. 2) the strategy of the head as an administrator, especially in managing finances. Principals are very creative in thinking of strategies to get additional income, namely principals and teachers managing school canteens, school cooperatives, and teaching computer lessons to students. This strategy can improve the welfare of non-civil servant teachers. 3) The form of welfare provided by the principal to teachers includes financial compensation and non-financial compensation. Based on the results of the study, it was concluded that the welfare of teachers at SD Negeri Luwungragi 02 was good, because the principal really thought of a mature strategy for the welfare of non-civil servant teachers. Keywords: Principal, Strategy, Welfare.